2009
DOI: 10.1088/0957-0233/21/2/022001
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for increasing the operating frequency range of vibration energy harvesters: a review

Abstract: This review presents possible strategies to increase the operational frequency range of vibration-based micro-generators. Most vibration-based micro-generators are spring-mass-damper systems which generate maximum power when the resonant frequency of the generator matches the frequency of the ambient vibration. Any difference between these two frequencies can result in a significant decrease in generated power. This is a fundamental limitation of resonant vibration generators which restricts their capability i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
352
0
2

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 572 publications
(369 citation statements)
references
References 39 publications
1
352
0
2
Order By: Relevance
“…Small changes in ambient frequency may be accommodated by a wider bandwidth low Q-factor harvester. More significant changes in ambient frequency could require a tuneable solution that can track the ambient frequency [10]. Alternatively, in some applications a harvester that exhibits non-linear behaviour (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Small changes in ambient frequency may be accommodated by a wider bandwidth low Q-factor harvester. More significant changes in ambient frequency could require a tuneable solution that can track the ambient frequency [10]. Alternatively, in some applications a harvester that exhibits non-linear behaviour (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Some project solutions regard to tuning a device to the resonance (Challa et al, 2008;Eichhorn et al, 2009) that can be accomplished by mechanical, magnetic and piezoelectric adjustments (Peters et al, 2009;Tang et al, 2013). The mechanical adjustment requires known excitation frequency and high cost energy to tuning, magnetic adjustment has limited tuning result and faces a limited micro sizing requirements, and the piezoelectric adjustment is a promising frontier to enhance energy harvesting capability (Zhu et al, 2010). First studies using piezoelectric adjustment results in negative net output power (Roundy and Zhang, 2005) but latter studies from Zhu et al (2010) found a mistake in Roundy and Zhang (2005) formulation that not considered mean voltage to active power determination.…”
Section: Introductionmentioning
confidence: 99%
“…for use on a helicopter [6]), but have so far been designed to harvest energy from fixed-frequency vibrations. Recent research has proposed vibration harvesters that are able to adjust their resonant frequency [7], but there is a need to consider the impact of this at the system level (rather than simply adding an adaptive generator to an existing system).…”
Section: Introductionmentioning
confidence: 99%